2017
DOI: 10.11648/j.ajim.20170503.11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of NPM1-A (Nucleophosmin1-A) Mutation in Iraqi Adult Acute Myeloid Leukemia Patients; Its Correlation with Clinicopathological Parameters

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy of myeloid progenitor cells characterized byanomalous proliferation, inhibition of differentiation and expansion of leukemic cells blocked at the early stage of hematopoiesis. The molecular markers have become a smart tool to further division of AML patients into subgroups. Nucleophosmin (NPM1) mutations are found in approximately 30% of adult AML patients and are associated with a favorable outcome when detected in absence of FLT3-ITD mutation. Over 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
2
0
3
Order By: Relevance
“…Many of Iraqi and international studies showed that the more than half of adult patients had hepatomegaly, splenomegaly or lymph nod enlargement at diagnosis that could be appreciated with physical examination also that the degree of organomegaly was more noticeable in children than in adults. Bone pain appeared in the acute myeloid leukemia cases is nearly similar to other Iraqi studies [19,9]. Bone pain is a direct consequence of bone marrow expansion.…”
Section: Discussionsupporting
confidence: 83%
“…Many of Iraqi and international studies showed that the more than half of adult patients had hepatomegaly, splenomegaly or lymph nod enlargement at diagnosis that could be appreciated with physical examination also that the degree of organomegaly was more noticeable in children than in adults. Bone pain appeared in the acute myeloid leukemia cases is nearly similar to other Iraqi studies [19,9]. Bone pain is a direct consequence of bone marrow expansion.…”
Section: Discussionsupporting
confidence: 83%
“…This close to Notopuro et al 21 with blast cells of (79.5%). Patients with NPM1 mutation had significantly higher WBC count mean (49.56±15.77×10*9/L) as compared with AML without any mutation (29.36±16.52×10*9/L) similar to findings of Döhner et al and 22 but different from Abdulateef et al 16 which reported that WBC count was non-significantly higher than in non-mutated group. Despite low mean of RBC count, hemoglobin levels and platelets count in AML patients, there were no significant difference among different groups, low levels of these parameters is a logical consequence with AML which is a cancer of the myeloid linage of blood cells, characterized by the rapid growth of abnormal cells that impede normal blood cell production and this will cause anemia, pallor and bleeding tendency.…”
Section: Discussionsupporting
confidence: 75%
“…However, Chauhan et al 15 disagree in reporting FLT3-ITD mutation in males more than females. NPM1 mutation was found in (10.34%) of the patients and this was not so far from Abdulateef et al 16 who detected it in (18.86%) of the patients. NPM1 mutation was reported more in males in (16.1%) of them than in females (3.7%), this results are similar to Abdulateef et al 16 with a detection in (28.1%) of males and (4.7%) of females.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…3,23 As for the NPM1 mutation, our findings are consistent with that of others in which no significant differences were observed between the mean full blood count values and the mutation status. 22,24 Likewise, we did not find any significant association between hyperleukocytosis, severe anaemia, and severe thrombocytopenia, and the mutation. However, Abdullah et (2020) showed that their patients with NPM1 mutation had significantly lower haemoglobin levels.…”
Section: Discussioncontrasting
confidence: 57%